Relationship of Loading/Discharging Equipment Facilities and Labour Competence on Work Productivity PT.Temas Depot Tembang 2024 - Alif Dafa Ramadhan; Bhanu Irsyad Radityo; Riza Syafrizal Citasuara; Honny Fiva Akira Sembiring (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to examine the relationship between loading and discharging equipment facilities, labor competence, and work productivity at PT Temas Depot Tembang. The research was conducted with a quantitative approach through observation, interviews, and questionnaires involving 32 workers. The findings indicated a significant correlation between the facilities used for loading and discharging equipment, labor competence, and work productivity. It is expected that improving facilities and worker competence will help overcome operational constraints and increase work productivity. Data analysis using the saturated sample technique was conducted using SPSS to identify correlations between variables that support the hypothesis that improvements in both aspects will contribute positively to work productivity.